2007
DOI: 10.1111/j.1478-3231.2007.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biophysical assessment of MTX‐induced liver fibrosis in psoriasis patients: Fibrotest predicts the presence and Fibroscan® predicts the absence of significant liver fibrosis

Abstract: In this population, Fibrotest accurately predicted the presence of significant liver fibrosis while the Fibroscan accurately predicted the absence of significant liver fibrosis in MTX users. This suggests that a combination of Fibrotest and Fibroscan should prospectively be evaluated in monitoring and detecting significant MTX-induced liver fibrosis in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 32 publications
(60 reference statements)
3
73
1
1
Order By: Relevance
“…In a study performed in the Netherlands [15] , using a cutoff value of 7.1 kPa, 88% of the patients who did not have significant fibrosis (F < 2 Metavir) were correctly identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study performed in the Netherlands [15] , using a cutoff value of 7.1 kPa, 88% of the patients who did not have significant fibrosis (F < 2 Metavir) were correctly identified.…”
Section: Discussionmentioning
confidence: 99%
“…All studies show that, by using a cut-off value of 6.8-7.5 kPa, we could identify accurately enough the patients who need to be treated (F ≥ 2 Metavir) vs those who should not be treated (F < 2 Metavir), and this without performing a LB [13][14][15] . The PPV of 98% obtained in our study for a cut-off value of 6.8 kPa suggests that we can quite accurately identify patients who must be treated (F ≥ 2 Metavir).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of MTX in psoriatic patients should be carefully monitored for the possible worsening of a pre-existing steatohepatitis [24] . Thus, in MTX users, FibroTest can accurately predict the presence of liver fibrosis and the Fibroscan significantly predict the absence of significant liver fibrosis [106] . CsA is a potent immunosuppressor used for organ transplantations and various autoimmune disorders; one of the most detectable side effects is hepatotoxicity [107] .…”
Section: Conventional Psoriatic Treatments and Liver Function Implicamentioning
confidence: 99%
“…Vergniol et al (Vergniol et al 2009) suggested that Fibroscan(r) should be useful for assessing treatment efficacy in clinical trials of new drugs. Recently, Berends et al (Berends et al 2007) reported that Fibroscan(r) accurately predicted the absence of significant liver fibrosis in methotrexate users.…”
Section: Treatment Follow-upmentioning
confidence: 99%